Small Elegies for America (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
Miniatures open us up to childhood memories, daydreaming, and nostalgia, but they can also alert us to the dangers and disappointments of our times. Many contemporary artists are utilizing small-scale artworks to represent difficult truths of contemporary American life, such as alienation, disenchantment, precarious housing, and economic insecurity writ large. In this essay, focusing on the artists Michael Paul Smith, Thomas Dolye, and James Casebere, the imaginations that encircle homes, neighborhoods, and small towns are complicated through utopian and dystopian art works that draw attention to past attachments to the future and the need for large changes now.